Effect of incentive payments on chronic disease management and health services use in British Columbia, Canada: Interrupted time series analysis. Issue 2 (February 2018) - Lavergne, M. Ruth; Law, Michael R.; Peterson, Sandra; Garrison, Scott; Hurley, Jeremiah; Cheng, Lucy; McGrail, Kimberlyn
Highlights: The province of British Columbia implemented incentive payments to primary care physicians for chronic disease management. There were no concurrent changes to the payment system, delivery model, or quality measurement. We observed limited impact on care processes among patients with hypertension following incentive introduction. We found no increase in primary care visits or continuity and no consistent evidence of reduced hospitalizations or costs. Abstract: We studied the effects of incentive payments to primary care physicians for the care of patients with diabetes, hypertension, and Chronic Obstructive Pulmonary Disease (COPD) in British Columbia, Canada. We used linked administrative health data to examine monthly primary care visits, continuity of care, laboratory testing, pharmaceutical dispensing, hospitalizations, and total h ealth care spending. We examined periods two years before and two years after each incentive was introduced, and used segmented regression to assess whether there were changes in level or trend of outcome measures across all eligible patients following incentive introduction, relative to pre-intervention periods. We observed no increases in primary care visits or continuity of care after incentives were introduced. Rates of ACR testing and antihypertensive dispensing increased among patients with hypertension, but none of the other modest increases in laboratory testing or prescriptions dispensed reached statistical significance. Rates of hospitalizations for stroke and heart failure among patients with hypertension fell relative to pre-intervention patterns, while hospitalizations for COPD increased. Total hospitalizations and hospitalizations via the emergency department did not change. Health care spending increased for patients with hypertension. This large-scale incentive scheme for primary care physicians showed some positive effects for patients with hypertension, but we observe no similar changes in patient management, reductions in hospitalizations, or changes in spending for patients with diabetes and COPD.